整合素α5β1介导细胞外信号调节激酶信号转导通路对A549细胞生长和侵袭的影响 (Zhongguo Fei Ai Za Zhi, 2011)
BACKGROUND AND OBJECTIVE: Recent studies have shown that integrin α5β1 as a core in the integrin family plays an important role in metastasis, invasion and poor difference of non-small cell lung cancer. In this study, A549 cells were cultured and treated with integrin α5β1 small interfering RNA (siRNA) and extracelluar signal-regulated protein kinase (ERK) inhibitor PD98059 to investigate the effect of integrin α5β1 on proliferation and migration of A549 cells and explore its signal transduction mechanism. METHODS: A549 cells were divided into four groups: Untransfection, Lipofectamine, Integrin α5β1 siRNA-transfected group and PD98059 group. The protein expression levels of integrin α5β1 were detected by Western blot analysis and the expression levels of integrin α5β1 mRNA was measured by reverse transcription-polymerase chain reaction (RT-PCR). The protein expression level of ERK1/2, MMP-9 and caspase-3 were measured by Western blot analysis. The proliferation and apoptosis of A549 cells were measured by MT assay and Annexin-V FITC PI double staining. RESULTS: Integrin α5β1 siRNA could inhibit the phosphorylated ratio of ERK by down-regulate the expression of ERK 1/2 proteins. In addition, integrin α5β1 siRNA or PD98059 could inhibit the proliferation of A549 cells, induce the apoptosis of A549 cells, upregulate the expression of caspase-3 and down-regulate the expression of MMP-9. CONCLUSION: Integrin α5β1 might involves the abnormal proliferation and migration of A549 cells through mediating ERK signal transduction pathway.